(untitled) (Proceedings of the International Conference on Public Health, 2017)
The Core Adult Tobacco Survey (CATS) is developed from the Philippine Global Adult Tobacco Survey (GATS), which was a nationally representative household survey of all non-institutionalized men and women aged 15 years and older. Its main objective is to determine tobacco smoking prevalence at the city level. Baguio City has shown its determination to the anti-smoking campaign but there were no local baseline data to evaluate its effectiveness. There were 100 households included in the study and 162 individual respondents completed the interview. The overall prevalence of current cigarette smoking is 27.2%. The prevalence of second hand exposure at home is 45.1% and at work is 27.2%. Exposure to any cigarette advertising is 34% and exposure to any cigarette promotion is 32.1%. Health warnings on cigarette packages was noticed by 97.7% of the smokers during the past 30 days, but only 60% of them reported that the warnings led them to think about quitting. The prevalence of smoking in the city was almost similar with the prevalence of smoking in the country. This baseline prevalence provides useful information to the policy makers for reviewing policies and program formulation.